Running Dictation as an Active Learning Strategy to Enhance Descriptive Writing in EFL Classrooms - Yunice Mamoribo; Rizqi Claudia Wardani. H (TEKILA: Journal of Language Teaching and Literature, 2025)
This study investigates the effectiveness of the Running Dictation technique in improving students’ writing skills, particularly in composing descriptive texts, among eighth-grade students at SMP Negeri 8 Doom. The objective of this research is to determine whether this active, collaborative strategy significantly enhances students' writing performance and learning interest. Employing a pre-experimental design with a one-group pre-test and post-test model, ten students participated in a series of instructional sessions utilizing Running Dictation as the core method. Data were collected through descriptive writing tests and a student interest questionnaire. Quantitative analysis using a paired sample t-test revealed a statistically significant improvement in writing scores, increasing from a pre-test mean of 60.00 to a post-test mean of 72.02 (p = 0.011). Additionally, 80% of students reported high to very high interest in the learning process, indicating strong engagement and motivation. These findings suggest that Running Dictation is an effective and enjoyable strategy for enhancing writing competence in English as a Foreign Language (EFL) context. The study offers practical implications for language teachers seeking interactive, low-cost methods to improve student writing outcomes.